Sustainable Development through Student Engagement: Innovations and Initiatives in Higher Education - Jain, Trilok Kumar; Jain, Nirupa (Journal of Advanced Research in English & Education; Vol 8 No 4 (2023): Journal of Advanced Research in English and Education, 2023)
Sustainable development is the development of society without compromising the future. Every higher educational institution must strive to prepare students for this. This can be best achieved through student engagement. Student engagement include activities, events, initiatives whereby the students are able to do something good for the society and internalize the goals of sustainable development. A case study is presented with examples about how collegiate system is being used to create impact making student engagements for sustainable development. The pursuit of sustainable development is imperative for the well-being of future generations, and higher education institutions play a crucial role in shaping responsible global citizens committed to this cause. This paper explores the pivotal role of student engagement as a catalyst for sustainable development in higher education. Student engagement encompasses a spectrum of activities, events, and initiatives that empower students to contribute positively to society while internalizing the principles of sustainable development. Through a detailed case study of Suresh Gyan Vihar University, this article illustrates innovative approaches, such as the collegiate system, employed to foster impactful student engagements aimed at sustainable development. The study emphasizes the importance of integrating diversity, innovation, creativity, and cultural awareness into academic initiatives, marking a paradigm shift towards an environmentally conscious and inclusive educational framework. The identified keywords—sustainable development, university, academics, student engagement, diversity, innovation, creativity, and culture—underscore the multifaceted nature of the strategies discussed herein, emphasizing their potential to drive positive societal transformation.